A Mobile Unit Synchronization Algorithm - A Partial Database Synchronization Scheme between a Centralized Server and Mobile Units - Gustafsson, Thomas; Hammarberg, Erik (My University, 2011)
This report covers the development of a new synchronization module for the Jetas Quality Systems AB. The developers at the company did not appreciate the existing module, based on Microsoft Synchronization Framework and thus this project was launched. The project first conducted a literature study to try to find a previously developed model that could be adapted to the Jetas system. This, unfortunately, was unsuccessful and the project continued with the design of a conceptual model for a synchronization module based on the Jetas systems characteristics. This model was implemented and enhanced iteratively and functionality added according to the prioritizations done in the requirements specification. The synchronization algorithm itself is an optimistic timestamp based method. It utilizes the synchronization primitives that are already present in the Jetas database and used by other parts of the system as well. The selection of which data to synchronize, so as to only do incremental updates each synchronization, is done by keeping track of the timestamps of the last time a synchronization was performed by that PDA while each database row has a timestamp of when it was last changed. Conflict detection is performed by comparing the timestamps of uploaded and server version of the DataRow in question. The module developed was tested in an office environment, but in this environment it showed a slight improvement in performance even while database indexes are optimized for the previous synchronization module and several optimizations can be done before this prototype is finalized for a production environment. In addition to this, the new synchronization module can easily be extended to implement new functionality, such as multiple users per PDA.
Keywords: Information Technology; Informationsteknik